2001
DOI: 10.1182/blood.v98.1.125
|View full text |Cite|
|
Sign up to set email alerts
|

Defective binding of factor XI–N248 to activated human platelets

Abstract: Variants of factor XI containing Gln226 to Arg (Q226 to R) and Ser248 to Asn (S248 to N) substitutions were first identified in an African American family with a history of excessive bleeding. The substitutions have recently been identified in unrelated individuals, suggesting they are relatively common. Both amino acids are located in the third apple domain of factor XI, an area implicated in binding interactions with factor IX and activated platelets. Recombinant factor XI-R226 and factor XI-N248 were compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…We were able to study eleven of the repeat mutations, with haplotype analysis showing that at least three, G460R (p.G478R), C398Y (p.C416Y) and the 2 bp deletion at codon 303 (p.321), had arisen independently and were not the result of a founder mutation. Two patients were initially assigned to have a Q226R (p.Q244R) mutation, however, on revision it was ascertained that this had been previously identified as a polymorphism (Sun, et al, 2001). Further investigation identified an alternative causative mutation in one patient, whilst it was determined that the other patient did not have inherited FXI deficiency.…”
Section: Resultsmentioning
confidence: 99%
“…We were able to study eleven of the repeat mutations, with haplotype analysis showing that at least three, G460R (p.G478R), C398Y (p.C416Y) and the 2 bp deletion at codon 303 (p.321), had arisen independently and were not the result of a founder mutation. Two patients were initially assigned to have a Q226R (p.Q244R) mutation, however, on revision it was ascertained that this had been previously identified as a polymorphism (Sun, et al, 2001). Further investigation identified an alternative causative mutation in one patient, whilst it was determined that the other patient did not have inherited FXI deficiency.…”
Section: Resultsmentioning
confidence: 99%
“…To confirm and extend our understanding of this interaction, we developed a solid phase binding assay for examining FXI binding to glycocalicin. cific, reversible, high affinity (K d app ϭ ϳ10 nM) FXI-binding sites (n ϭ 1,500 sites/platelet) that require the presence of HK and ZnCl 2 , whereas in the presence of ZnCl 2 without added HK, FXI binds to about half this number of sites with similar affinity (9,19,21 (19,21,24) and because the FXI-binding site on platelets is in the GPIb␣ subunit of the GPIb-IX-V complex, we initially determined whether glycocalicin (the soluble form of GPIb␣) interacts with the Apple domains by examining the capacity of each of the recombinant, expressed Apple domains of FXI to compete with FXI for binding to glycocalicin in our solid phase assay. Fig.…”
Section: Zncl 2 -Dependent Binding Of Factor XI To Glycocalicin-thementioning
confidence: 99%
“…Specific ligand-binding functions have been attributed to each of the four FXI Apple domains (1,(15)(16)(17)(18)(19)(20) including the A3 domain, which has been shown to bind the platelet (19,21), heparin (22), and FIX (23). We have previously shown that specific amino acids in the A3 domain (Ser ) mediate the binding of FXI to platelets (21,24), whereas amino acids juxtaposed to the plateletbinding site (Lys 252 and Lys…”
mentioning
confidence: 99%
“…However, rs5969 was associated with FXI activity levels comparable to wildtype when tested in an APTT-based assay (Martincic et al 1998). In line with this, the catalytic efficiency (kcat) for FIX activation was shown to be comparable to that of wild-type FXI, thus normalising the APTT result (Sun et al 2001). Various clinical studies as well as studies that examined the structural features of rs5969 have confirmed the minimal effect (Mitchell et al 1999;Mitchell et al 2003;O'Connell et al 2005;Mitchell et al 2006;Saunders et al 2009).…”
Section: Non-synonymous Variantsmentioning
confidence: 57%
“…Besides being compound heterozygous for type II (rs121965063, p.Glu135Ter) and type III (rs121965064, p.Phe301Leu) variants, the abnormal control did not contain the other two non-synonymous variants. The binding affinity between FXI and FIX (Km) differed considerably from wild-type FXI (Sun et al 2001). However, rs5969 was associated with FXI activity levels comparable to wildtype when tested in an APTT-based assay (Martincic et al 1998).…”
Section: Non-synonymous Variantsmentioning
confidence: 99%